2014
DOI: 10.1007/s11103-014-0251-4
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis drought-induced protein Di19-3 participates in plant response to drought and high salinity stresses

Abstract: Di19 (drought-induced protein19) family is a novel type of Cys2/His2 zinc-finger proteins. In this study, Arabidopsis Di19-3 was functionally characterized. The experimental results revealed that AtDi19-3 is a transcriptional activator, and could bind to the TACA(A/G)T sequence. AtDi19-3 expression in plants was remarkably induced by NaCl, mannitol and abscisic acid (ABA). T-DNA insertion mutation of AtDi19-3 results in an increase in plant tolerance to drought and high salinity stresses and ABA, whereas overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…Only GO categories with a false discovery rate value , 0.05 were included. C, Heatmap showing coexpression patterns for ABA signaling pathway by phosphorylating ABAresponsive element binding protein factors ABF1 and ABF4 (Hayashi et al, 2001;Milla et al, 2006;Ma and Bohnert, 2007;Sherameti et al, 2008;Liu et al, 2013;Qin et al, 2014;Song et al, 2016).…”
Section: Analysis Of Selected Protein Interactorsmentioning
confidence: 99%
“…Only GO categories with a false discovery rate value , 0.05 were included. C, Heatmap showing coexpression patterns for ABA signaling pathway by phosphorylating ABAresponsive element binding protein factors ABF1 and ABF4 (Hayashi et al, 2001;Milla et al, 2006;Ma and Bohnert, 2007;Sherameti et al, 2008;Liu et al, 2013;Qin et al, 2014;Song et al, 2016).…”
Section: Analysis Of Selected Protein Interactorsmentioning
confidence: 99%
“…Overexpression of GmDi19-5 displayed increased sensitivities to salt, drought, and oxidative stress during the germination and seedling stages in Arabidopsis (Figures 7 , 8 ). Recently, it was reported that AtDi19-3 displayed drought- and salt-sensitive phenotype in overexpression lines (Qin et al, 2014 ). Similar to AtDi19-3, GmDi19-5 might act as a negative regulator in response to salt and drought stresses (Qin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This motif contains two cysteines and two histidines that serve as zinc ligands and is represented by the signature Cys-X 2,4 -Cys-X 12 -His-X 3,4,5 -His (Brown et al, 1985 ; Miller et al, 1985 ; Pabo et al, 2001 ; Sakamoto et al, 2004 ). Drought-induced (Di19) proteins are zinc finger transcription factors that play important roles in development, growth, and response to stress (Milla et al, 2006 ; Li et al, 2010a , b ; Liu et al, 2013b ; Qin et al, 2014 ). Di19 proteins are encoded by a small gene family that numbers seven isoforms in Arabidopsis and five in rice (Milla et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations